2007
DOI: 10.1038/nrm2125
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases and the regulation of tissue remodelling

Abstract: Matrix metalloproteinases (MMPs) were discovered because of their role in amphibian metamorphosis, yet they have attracted more attention because of their roles in disease. Despite intensive scrutiny in vitro, in cell culture and in animal models, the normal physiological roles of these extracellular proteases have been elusive. Recent studies in mice and flies point to essential roles of MMPs as mediators of change and physical adaptation in tissues, whether developmentally regulated, environmentally induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
2,180
2
52

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 2,561 publications
(2,317 citation statements)
references
References 180 publications
31
2,180
2
52
Order By: Relevance
“…Several reports in recent years have demonstrated that various MMPs act on non-matrix proteins, such as cytokines, chemokines, receptors, antimicrobial peptides, and more ). Thus, MMPs should not be viewed solely as proteinases of matrix catalysis, but rather as extracellular processing enzymes involved in regulating cell-cell and cell-matrix signaling events, quite typically, gain-of-function processing of latent proteins (Page-McCaw et al, 2007;Parks, 1999;Vu and Werb, 2000).…”
Section: Regulation Of Mmp Activitymentioning
confidence: 99%
“…Several reports in recent years have demonstrated that various MMPs act on non-matrix proteins, such as cytokines, chemokines, receptors, antimicrobial peptides, and more ). Thus, MMPs should not be viewed solely as proteinases of matrix catalysis, but rather as extracellular processing enzymes involved in regulating cell-cell and cell-matrix signaling events, quite typically, gain-of-function processing of latent proteins (Page-McCaw et al, 2007;Parks, 1999;Vu and Werb, 2000).…”
Section: Regulation Of Mmp Activitymentioning
confidence: 99%
“…The degradative functions of MMPs are critical in tissue remodeling, most notably in wound repair. 5 In addition to their enzymatic cleavage of matrix proteins, MMPs are able to activate cytokines, growth factors, and cell surface receptors, the last by limited proteolytic processing. 6 Based on their multiple biological activities, MMPs are thought to participate in a diverse range of pathological processes, including rheumatoid arthritis and fibrosis of the liver, kidneys, heart, and lungs.…”
Section: Idiopathic Pulmonary Fibrosis (Ipf) May Be Triggered By Epitmentioning
confidence: 99%
“…This review intends to discuss diverse functions of metalloproteinases implicated in cancer progression. Due to space constraints, we have chosen to concentrate our efforts on ADAMs and ADAMTSs, since MMPs have been extensively described in previous reviews [4][5][6][7][8][9]. Here, following a brief description of ADAMs and ADAMTSs, we explore their contribution to different steps of cancer progression.…”
Section: Introductionmentioning
confidence: 99%